Accepted or rejected: A destiny of publication hunter - Sumarno Adi Subrata; Sara Concepcion Maury Mena; Sant Nathoo (Journal of Holistic Nursing Science, 2023)
Having understandable and clear-precise writing is fundamental for nurses who dive into a publication world. However, writing skills for publishing are not always part of the curriculum in many healthcare education systems globally. The writing skills must be adapted to successfully prepare for publishing in the scientific literature and presenting oral and written summaries of our research. Accepted or rejected is a part of the journey of the publication hunter. The author should understand the “rule of the game” of publication to minimize or avoid rejection in a high-standard nursing journal. Psychological preparation is also essential, as several authors feel pessimist after having a rejection. These phenomena need to be considered for a journal editor to massively educate the author about how to write a paper, how to describe gaps of knowledge, and how to explain the research method in the method section. Even though this process requires a long-time step, I think this would not be a big deal for the author. They will always try and try to achieve a publication in the highest-impact nursing journal. No matter how complicated the process is, being an optimist is always needed for those writing a publication. Keywords: accepted; rejected; publication; academic writing; nursing carreer